Herbicidal Activity of Essential Oils on the Germination of Some Problem Weeds - UREMIS, I.; ARSLAN, M.; SANGUN, M.K. (Asian Journal of Chemistry, 2010)
The herbicidal activities of volatile compounds of plant origin (sweet basil, Ocimum basilicum L.; common sage, Salvia officinalis L.; English lavender, Lavandula angustifolia Mill.; lemon balm, Melissa officinalis L. and common thyme i.e., Thymus vulgaris) were studied against 3 weeds (common cocklebur, Xanthium strumarium L.; sterile wild oat, Avena sterilis L. and short spiked canarygrass, Phalaris brachystachys L.) in laboratory experiments. Chemical composition of the essential oils were determined by capillary gas chromatography (GC) and GC/MS. The essential oil composition varied with the species. Thymol, geranial and β-thujone were the main constituent of T. vulgaris, M. officinalis and S. officinalis oils, respectively. Linalool was the main constituent of O. basilicum and L. angustifolia oils. Each essential oil was applied at the concentrations of 2, 4, 8, 16 and 32 μL on the filter paper at the top of the Petri dishes to determine germination and growth bioassays. Inhibition rate of essential oils increased with the increasing concentrations. Essential oils of T. vulgaris had the highest inhibitory effect on the germination of X. strumarium and A. sterilis, on the other hand essential oil of O. basilicum had the highest inhibitory effects on the germination of P. brachystachys. Each essential oil suppressed seedling and root growth of the tested weeds. Essential oil of O. basilicum, S. officinalis, L. angustifolia, M. officinalis and T. vulgaris could be used as alternatives of herbicides to suppress germination of X. strumarium, A. sterilis and Phalaris brachystachys seeds in organic farming systems.